A shadow rate without a lower bound constraint - Rafael B. De Rezende; Annukka Ristiniemi (Sveriges Riksbank, 2018)
We propose a shadow rate that measures the expansionary (contractionary) interest rate effects of unconventional monetary policies that are present when the lower bound is not binding. Using daily yield curve data we estimate shadow rates for the US, Sweden, the euro-area and the UK, and find that they fall (rise) when market participants expect monetary policy to become more expansionary (contractionary), and price this information into the yield curve. This ability of the shadow rate to track the stance of monetary policy is identified on announcements of policy rate cuts (hikes), balance sheet expansions (contractions) and forward guidance, with shadow rates responding timely, and in line with government bond yields. We show two applications for our shadow rate. First, we decompose shadow rate responses to monetary policy announcements into conventional and unconventional monetary policy surprises, and assess the pass-through of each type of policy to exchange rates. We find that exchange rates respond more to conventional than to unconventional monetary policy. Lastly, a counterfactual experiment in a DSGE model suggests that inflation in Sweden would have been around 0.47 percentage points lower had the Riksbank not used unconventional monetary policy since February 2015.
Keywords: E43; E44; E58; E52; 330; unconventional monetary policy; monetary policy stance; term structure of interest rates; short-rate expectations; term premium